Influência da deformação na laminação de encruamento nas propriedades mecânicas do aço acalmado ao alumínio refosforado, galvanizado a quente classe 220mpa de limite de escoamento - Carlos Augusto Carvalhido (2007)
Votorantim Metais Zinco, a fully Brazilian company, belonging to the Votorantim group, is the only producer of zinc and lead in the country. The industrial operations are located in the state of Minas Gerais, divided in two mining enterprises, in Vazante and Paracatu, and two metallurgical plants, in Três Marias and Juiz de Fora. The ore from the Paracatu deposit contains lead and zinc sulphides, galena and sphalerite, respectively. The ore is extracted from an underground mine and sent to the concentrator to be processed in a sequence that involves crushing, grinding, lead flotation, zinc flotation and filtration. This investigation was performed with samples from the Paracatu deposit aiming at studying the influence of the dispersion of the particles in the pulp on lead and zinc flotation. Samples of ore and also of the minerals sphalerite, galena, pyrite, and dolomite were selected for the experiments. Nine types of dispersing agents and six combinations among them were employed. A set of three dispersing agents was selected for the flotation of lead and another set of three was chosen for zinc flotation. The criteria for the selection of reagents were: high dispersion degree for galena and low for the other species, high dispersion degree for sphalerite and low for the other species, low dispersion degree for pyrite and high for the other species and high dispersion degree for all species. Lead flotation experiments were performed under three conditions aiming at verifying the influence of the dispersing agent, of the pH, and of sodium carbonate. The zinc flotation test was carried out at pH = 10.5 modulated with lime. The use of dispersing agents in lead flotation did not improve the overall efficiency of the circuit for, despite improving the lead metallurgical recovery, they increase significantly the zinc losses in the lead concentrate. Sodium carbonate presented a low dispersion degree and did not affect the lead flotation results when compared with those achieved at natural pH and at pH = 9.8 modulated with lime. Two dispersing agents were particularly effective in zinc flotation: dispersant 3223 sodium polyacrylate and sodium hexametaphosphate. Both reagents significantly enhanced zinc recovery without impairing the quality of the concentrate.